Inovasi Manajemen Teknologi Berbasis Aplikasi Slims (Senayan Library Management System) Dalam Meningkatkan Layanan Pengguna Pada Perpustakaan Universitas Muhammadiyah Bima - muma, muarif; Umar, Umar; Anwar, Anwar (Jurnal Media Informatika, 2024)
Abstract− Traditional libraries with large collections will face difficulties in managing and controlling collections over time, because the number of collections tends to continue to increase. This causes users to take longer to find the information sources they need. In addition, access to the library is limited to the library's physical location and during certain operational times. Therefore, inclusive library services for the community require support from a computerized automation system that is ready to be used at any time, facilitating access to the required information sources. The location of this research was carried out at the Bima Muhammadiyah University Library, the aim of the research was to find out how the SliMS application was applied in technology management at the Bima Muhammadiyah University Library. This research used a descriptive quantitative design. The respondents in this research were students and the Bima Muhammadiyah University Academic Community as Library Members. totaling 155 people, the sampling technique in this research used random sampling. The data collection technique in this research was by observing, distributing questionnaires and documenting studies. Results of research conducted using a descriptive quantitative approach, Based on the research results, the application of the SLiMS application in technology management in the Bima Muhammadiyah University library is mostly positive. The Library Management Information System (SLiMS) application has become a popular solution for managing library collections digitally. Implementation of SLiMS in the Bima Muhammadiyah University Library is a strategic step to increase the efficiency and effectiveness of library services. The implementation of the SLiMS (Senayan Library Management System) application has a significant impact on the quality of services provided to library users. Keywords: Innovation, SLiMS Applications, Libraries, Services